A Study of the Relationship between Selected Personal Factors, Professional Practice Environment and Job Satisfaction of Registered Nurses in Thailand - Rerkluenrit, Juntima; Kodchakri, Rukchanok (Srinagarind Medical Journal, 2019)
Background and Objective: Relationship between selected personal factors, positive professional practice environment and registered nurses’ job satisfaction lead to effective nursing care and increasing quality of life in both registered nurses and patients. This study aimed to investigate the relationship between selected personal factors, professional practice environment, and job satisfaction of registered nurses in Thailand. Method: This descriptive correlational study design included the 2,340 registered nurses having experience more than 1 year. The data were collected using 3 electronic questionnaires which involved 1) selected personal data questionnaire, 2) professional practice environment questionnaire, and 3) registered nurses’ job satisfaction questionnaire. The data was conducted since 15 February to 31 May 2018. The data were statistically analyzed by using frequency, percentage, mean, standard deviation Pearson’s correlation coefficient and chi-square. Result: The 1,911 complete questionnaires showed that a statistically significant less than .05, correlation was found between age, nursing experience, job hours during one week ago, total hours in morning, afternoon and night period, and salary, and job satisfaction of professional nurses. Moreover, practice environment and job satisfaction of professional nurses were moderately correlated each other at level of significance less than .001. Conclusion: Job satisfaction of professional nurses in Thailand was related to selected personal factors and a positive relationship with the professional practice environment.